(3NdGUI GdCbhGd aj eYQaI GdQLGds - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eQTO GdYHGO Edi SHjd GdSOGO s
(3BNQgG (B:s
(3hGdMeO ddg hUdi Gddg Ydi NjQ NdbI s
(3QJHg Ydi bSejf hNGJeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B227 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B303s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B208 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B125 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI ajV Gddg (B(323) s
Keywords: (3GdJGQjNs